Faktor – Faktor Yang Mempengaruhi Siswa Memilih Jurusan Perhotelan di SMK Negeri 1 Magetan - Wahyu Tri Hastiningsih; Makmun Syaifudin (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
The candidates of vocational high school students often experience difficulties in choosing the majors they will take. There are several factors that influence in choosing a major. One of the majors at SMKN 1 Magetan is the hospitality department. This study aims to determine the factors that influence students' interest in choosing a hospitality major at SMKN 1 Magetan. This research used quantitative methods. The sample in this study were 100 students from the hospitality department of class X, XI, and XII. The sample technique used was random sampling. The research instrument used a questionnaire prepared by the researcher with 24 question items obtained from the results of the validity test r results > r table of 0.1654 at n = 100 and the reliability test results obtained 0.778 and 0.898. Of the 24 question items, there was 1 question which was declared invalid with a result r value of 0.109 <0.1654. The results of this study found that the majority of students have chosen the hospitality major because of the influence of friends with a percentage of 59 (59%), 23 (23%) from the web and the rest came from parents' encouragement, self-will and the surrounding environment.